Comparative and Correlational Evaluation of the Phytochemical Constituents and Antioxidant Activity of Musa sinensis L. and Musa paradisiaca L. Fruit Compartments (Musaceae) - Barnabas Oluwatomide Oyeyinka; Anthony Jide Afolayan (The Scientific World Journal)
Secondary metabolites and their biological activity have pharmacological relevance in the prevention and therapeutic management of disease, including the facilitation of normal physiological processes through biochemical mechanisms. In this study, phytochemical constituents and antioxidant activity were evaluated quantitatively on the acetone, ethanol, and aqueous extracts of the flesh, and peel, as well as the boiled peel extract compartments of Musa sinensis L. and Musa paradisiaca L. fruits. Total phenol, proanthocyanidin, and flavonoid contents were estimated and measured spectrophotometrically. The free radical scavenging antioxidant capacity of the extracts was tested on DPPH (2,2-diphenyl-1-picrylhydrazyl ethanol), ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)), and FRAP (ferric reducing antioxidant power) assay models. Correlation between phytoconstituents and antioxidant activity was analysed using Pearson’s coefficient. The results showed varying amounts of phytochemicals in the solvent extracts of the flesh and peel, including the boiled peel extract of M. sinensis and M. paradisiaca. All acetone extracts of M. sinensis flesh, M. paradisiaca flesh, and M. paradisiaca peel had the highest phytochemical contents, with the exception of the ethanol extract of M. sinensis peel which had the highest phenol content; just as on the overall scale, the peel compartments had generally higher phytochemical profiles than the soft flesh in both fruits. The boiled peel extracts of M. sinensis and M. paradisiaca had the highest ABTS (0.03 mg/mL) and DPPH (0.03 mg/mL) activity. Ferric reducing power (FRAP) was the highest in the ethanol extracts of M. sinensis flesh and peel, and M. paradisiaca flesh, while it was the highest in the acetone extract of M. paradisiaca at the peak concentration used (0.1 mg/mL). There was a significant negative correlation between the total phenol and flavonoid contents of M. sinensis flesh with its DPPH radical scavenging activity and proanthocyanidin content of M. paradisiaca flesh with its DPPH radical scavenging activity. The correlation outcomes indicate that none of the phytochemical constituents solely affected antioxidant activity; instead, a combination of the polyphenolic constituents contributed to antioxidant activity. This study shows the therapeutic potentials of the flesh and, importantly, the peel of M. sinensis and M. paradisiaca fruits on the basis of the polyphenolic constitution against free radicals and oxidative stress.